The Topological Type of Equilateral and Almost Equiangular Polygon Spaces - Yasuhiko Kamiyama (Journal of Mathematics)
Let Pn be the configuration space of equilateral spatial n-gons. For θ∈0,π and k∈0,1,…,n, let Pnkθ be the subspace of Pn consisting of elements whose first k bond angles are θ. Recently, the topological type of Pnkθ was determined for small n, special θ, and k=n or n−2. In this paper, we determine the topological type of Pnn−3θ for general n and θ.